Biomarkers of myocardial fibrosis and their genetic regulation in patients with heart failure - T. B. Pecherina; A. G. Kutikhin (Российский кардиологический журнал, 2020)
Currently, the development of chronic heart failure (CHF) is considered from the perspective of pathological structural remodeling of myocardium and fibrosis. Despite the widespread use of molecular genetic markers in clinical practice, only a small number of them are used to evaluate remodeling processes, as well as to predict potential complications associated with heart failure (HF). In addition, the relationship between many biomarkers with instrumental and histological confirmation of myocardial fibrosis has not yet been determined. Myocardial fibrosis remains quite debatable and controversial subject, which actualizes the further study of this direction. The discovery of pathogenetic and diagnostic markers of myocardial fibrosis could contribute to the development of targeted therapy. Of particular interest is the search for possible pathogenetic markers, since this is relevant for clinical practice.